Análise termo-oxidativa do biodiesel de girassol (helianthus annuus) - Tavares, Marileide Lira de Araújo (2009)
The present work aims at investing the biodiesel obtained from the transesterification of sunflower oil by means of alkaline catalysis using 30% of ethyl alcohol, 1% KOH for each 100g of oil and (1:6) oil/alcohol molar ratio. The overall content of ethyl esters (99.72%) was determined by gas chromatography coupled to mass spectrometer, confirm the efficiency of the purification process carried out after the biodiesel synthesis. In the physico-chemical analyses, the results obtained complied with the standards allowed by the Technical Regulation No. 7 from the Brazilian National Agency of Petroleum, Natural Gas and Biofuels (ANP). Thermal analyses were carried out with sunflower oil, diesel, sunflower ethanol biodiesel (B100) and its biodiesel/diesel blends, with proportion of 5, 15, 20, 25 and 50% biodiesel, employing the heating rate of 10 °C.min-1 in atmospheres of air and nitrogen, with runs up to 600 °C. The thermal decomposition of the samples was studied from the TG curves, aiming at assessing the order of thermal stability of the samples. The antioxidants α-tocopherol, BHT and TBHQ were added to the biodiesel samples aiming at assessing their efficiency in improving the thermo-oxidative stability of biodiesel. The techniques of pressure differential scanning calorimetry (PDSC) and Rancimat, revealed that the most indicated antioxidants for the storage of the ethanol sunflower oil biodiesel are BHT and TBHQ. However, even showing an antioxidant activity when added to the ethanol sunflower oil biodiesel, BHT was not efficient enough to increase the induction period to the minimum value of 6 hours at 110 ºC, as determined by ANP. The kinetic parameters of activation energy (Ea) and pre-exponential factor (A) were determined utilizing the Arrhenius equation, from data obtained in the isothermal thermogravimetric curves.